Combining globally search for a regular expression and print matching lines with bibliographic monitoring of genomic database improves diagnosis - Tran Mau-Them, Frédéric; Overs, Alexis; Bruel, Ange-Line; Duquet, Romain; Thareau, Mylene; Denommé-Pichon, Anne-Sophie; Vitobello, Antonio; Sorlin, Arthur; Safraou, Hana; Nambot, Sophie; Delanne, Julian; Moutton, Sebastien; et al. (Frontiers in Genetics, 2023)
Exome sequencing has a diagnostic yield ranging from 25% to 70% in rare diseases and regularly implicates genes in novel disorders. Retrospective data reanalysis has demonstrated strong efficacy in improving diagnosis, but poses organizational difficulties for clinical laboratories. We applied a reanalysis strategy based on intensive prospective bibliographic monitoring, and directly applied the Globally search for a Regular Expression and Print matching lines (GREP) command-line tool to a large ES database. For 18 months, we submitted daily the same 5 keywords of interest ((intellectual disability, (neuro)developmental delay, (neuro)developmental disorder)) to PubMed, to identify recently published, novel disease-gene associations, or new phenotypes in genes already implicated in human pathology. We used the Linux GREP query and an inhouse script, to collect all variants in these genes from our 5459 exome database. After GREP queries and variants filtration, we obtained 128 genes and collected 56 candidate variants in 53 individuals. We confirmed causal diagnosis for 19/128 genes (15%) in 21 individuals, and identified variants of unknown significance for 19/128 genes (15%) in 23 individuals. Altogether, the GREP queries of only 128 genes during a period of 18 months permitted to establish a causal diagnosis in 21/2875 undiagnosed affected probands (0.7%). The GREP query is efficient, and less tedious than complete periodical reanalysis. It is an interesting reanalysis strategy to improve diagnosis.